Development of Phys-FLUIDS Learning Media to Improve Problem Solving Skills of Prospective Physics Teacher Students - Setiani, Rahyu; Syafiah, Rohmatus; Dwikoranto; Thoriq Lintangesukmanjaya, Rahmatta; Aufansyah Putra, Dedy; Zahro, Fatimatuz; N. Bergsma, Lindsay (Proceeding of International Joint Conference on UNESA, 2025)
The study aims to analyze the validity results of the development of Phys-FLUIDS (Physics-Fundamental Learning & Ultimate Insights in Dynamic Statics) to improve the problem-solving skills of prospective physics teacher students. The study was structured as R&D development research, employing the Borg and Gall model approach. In the needs analysis stage, samples were obtained from several physics students at Surabaya State University. The validity of Phys-FLUIDS was assessed through a product test with three expert validators in their respective fields. The study’s results indicate that Phys-FLUID was developed to meet the very valid category, with an average Aiken’s value score of 0.90, serving as a teaching material to improve the problem-solving skills of prospective teacher students. With the construction of materials, questions, problem reasoning, problem-solving approaches, and attractive designs, Phys-FLUIDS can increase the enthusiasm of prospective teacher students in providing effective teaching in the classroom. Phys-FLUID is designed in the form of E-Books and conventional books, which are considered less dynamic and interactive. Therefore, it is recommended that Phys-FLUIDS be developed in a virtual application design. Although this research is limited in its development design, which only reaches the validation stage, it can provide a clear picture of whether the Phys-FLUIDS developed meets the very valid category.